Prevalence of Toxoplasma gondii in Pregnant Women’s Population in District Karak of Khyber Pakhtunkhwa, Pakistan (Journal of Medical & Health Sciences Review, 2025)
About 30–50% of the global human population is infected with toxoplasmosis, which is caused by the protozoan parasite Toxoplasma gondii. The aim of this study was to determine the prevalence of Toxoplasma gondii and its associated risk factors among pregnant women in District Karak. A total of 300 blood samples were collected from pregnant women in different areas of District Karak between September 2023 and December 2023 using the Onsite Toxo IgG/IgM Rapid Test Kit. Demographic information, risk factors, and toxoplasmosis-related symptoms were analyzed. The overall prevalence of T. gondii was 22.67% for toxo-IgG and 20.33% for toxo-IgM, which was not statistically significant (p=0.4867). The highest prevalence was recorded in the 20–30-year age group (26.26% for toxo-IgG and 23.23% for toxo-IgM), while the lowest prevalence was observed in women under 20 years (18.33% and 16.66% respectively). Tehsil Banda Daud Shah showed the highest prevalence, while Tehsil Karak had the lowest. Lower-class families exhibited higher prevalence rates (28.57% for toxo-IgG and 26.43% for toxo-IgM) than upper-class families (13.33% and 10% respectively). The presence of cats in households was associated with the greatest prevalence rates (30% for toxo-IgG and 28% for toxo-IgM). Miscarriages were reported in 30/100 (30%) for toxo-IgG-positive and 27/100 (27%) for toxo-IgM-positive pregnant women. In conclusion, the present study highlights the need for special control measures and increased public awareness to minimize the spread of Toxoplasma gondii in the area.